2021
DOI: 10.3390/min11070719
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigations Coupled to VIR/Dawn Observations to Quantify the Large Concentrations of Organic Matter on Ceres

Abstract: Organic matter directly observed at the surface of an inner planetary body is quite infrequent due to the usual low abundance of such matter and the limitation of the infrared technique. Fortuitously, the Dawn mission has revealed, thanks to the Visible and InfraRed mapping spectrometer (VIR), large areas rich in organic matter at the surface of Ceres, near Ernutet crater. The origin of the organic matter and its abundance in association with minerals, as indicated by the low altitude VIR data, remains unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…The shape of the 3.4-μm band and the lack of an associated 3.25-μm feature could exclude organics with a high content of aromatic carbon such as anthraxolites as main carriers of the features on Ceres, in favour of hydrocarbons rich in aliphatic carbon [25]. Laboratory studies have found organic-rich analogues that could reproduce absorption bands in the VIR spectra [117]. However, the exact nature and concentraton history of the organic matter is still unclear, making this a compelling scientific question for any future space mission to Ceres [117].…”
Section: Results From the Dawn Missionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the 3.4-μm band and the lack of an associated 3.25-μm feature could exclude organics with a high content of aromatic carbon such as anthraxolites as main carriers of the features on Ceres, in favour of hydrocarbons rich in aliphatic carbon [25]. Laboratory studies have found organic-rich analogues that could reproduce absorption bands in the VIR spectra [117]. However, the exact nature and concentraton history of the organic matter is still unclear, making this a compelling scientific question for any future space mission to Ceres [117].…”
Section: Results From the Dawn Missionmentioning
confidence: 99%
“…Laboratory studies have found organic-rich analogues that could reproduce absorption bands in the VIR spectra [117]. However, the exact nature and concentraton history of the organic matter is still unclear, making this a compelling scientific question for any future space mission to Ceres [117]. Furthermore, organic compounds possibly also exist on top of Cerealia Facula, the brightest spot located roughly in the middle of crater Occator [26].…”
Section: Results From the Dawn Missionmentioning
confidence: 99%
“…The comparison between the spectra of the organic-rich region of Ceres and that of Bennu shows different shape and depth. Ceres has a stronger band with clear minima at about 3.51 and 3.42 µm (see also [25]), while the minima of the organic band at Bennu are at 3.55 and 3.46 µm. The differences between the bands suggest that the mineralogy of the bodies is different and also the organics that characterize the surfaces of Bennu and Ceres have different composition.…”
Section: Similarities and Differences With C Asteroidsmentioning
confidence: 96%
“…A broad band at about 3.3-3.5 µm is also present in the spectrum, attributed to the contribution of different minerals, primarily carbonate and ammoniated phyllosilicates, but also organics. In particular, aliphatic organics contribute to that signature in the organic rich-regions (hundred km sized areas close to Ernutet crater), where the absorption at 3.3-3.5 dominates the spectrum [10,14,15,25].…”
Section: Ceres Compositionmentioning
confidence: 99%
See 1 more Smart Citation